Corporate Governance and Integrated Reporting: An Empirical Analysis of Mining Companies Listed on the Indonesia Stock Exchange - Risnawati, Henny; Jaelani, Achmad (Universitas Indo Global Mandiri, 2025)
This study aims to determine the effect of Corporate Governance proxied by Managerial Ownership, Institutional Ownership, Board of Directors, and Audit Committee on Integrated Reporting in mining companies listed on the Indonesia Stock Exchange. This study uses a quantitative research type associative approach, using the panel data regression analysis method with Eviews version 12. The population in this study are mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample was determined based on purposive sampling method, with a total sample size of 18 mining companies and 5 years of research period, so that the total observations in this study were 90 observations. The data collection technique uses the documentation method through the website www.idx.co.id and the company's official website. Hypothesis testing using the t test. The results showed that (1) Managerial Ownership has a significant positive effect on Integrated Reporting (2) Institutional Ownership has no effect on Integrated Reporting (3) The Board of Directors has a significant positive effect on Integrated Reporting (4) The Audit Committee has a significant positive effect on Integrated Reporting. The results of this study have implications for increasing manager involvement in the ownership structure and strengthening governance functions to improve reporting quality. This research also opens up opportunities to explore the reasons behind why institutional ownership has no effect, as well as identify other factors that could potentially affect the quality of integrated reporting. Keywords: Corporate Governance, Institutional Ownership, Board of Directors, Audit Committee, Integrated Reporting